Treatment outcomes and risk factors for severity and mortality in Clostridioides difficile infection: a single-center study in Thailand - Chaemprida, Thamonwan; Nasomsong, Worapong (The Journal of Infection in Developing Countries, 2025)
Introduction: Clostridioides difficile often causes hospital-acquired diarrhea, leading to unfavorable treatment outcomes. This study investigates CDI treatment outcomes and factors affecting severity and mortality at a university hospital in Thailand. Methodology: A retrospective study was conducted from June 2019 to December 2021. The primary endpoints were treatment outcomes with a 95% CI. Univariable and multivariable Cox regression analyses determined risk factors for severe CDI and 30-day mortality. Results: Of 187 patients receiving a diagnosis of and receiving treatment for CDI, 103 patients (55.8%) presented non-severe CDI, and 84 patients (44.2%) had severe CDI. The 30-day mortality rate of CDI was 24.1%, which was significantly higher in the severe group (36.9 vs. 13.6%, p ≤ 0.001). Multivariable analysis revealed the independent risk factor for severe CDI was chronic kidney disease (aOR 15.16, 95% CI 6.3, 36.48), and risk factors for all-cause mortality at 30 days were ICU admission (aOR 3.56, 95%CI 1.48, 8.56) and carbapenem exposure (aOR 2.79, 95% CI 1.17, 6.68). Conclusions: This study demonstrated high mortality rates and a significant incidence of refractory and recurrent infections in the severe CDI group. Chronic kidney disease was an independent risk factor for severe CDI. ICU admission and carbapenem exposure were independent risk factors for all-cause mortality.